GOVERNANCE OF AFRICAN STATE-OWNED ENTERPRISES (SOEs) – TOWARDS AGENDA 2063 - Ackers, Barry; Adebayo, Adeyemi (Accounting Profession Journal (APAJI), 2022)
Following centuries of institutionalised colonialism, Africa continues failing to drive socioeconomic growth and prosperity. Although the vestiges of Africa’s colonial legacy have certainly contributed to this malaise, Africa cannot continue blaming colonialism for its failure to develop. To reverse the downward spiral and provide the platform to achieve the goals of the African Union’s Agenda 2063, requires a return to Africa’s primary Ubuntu[1] values. Africa must accept that it can no longer remain passive participants, simply providing raw materials for beneficiation by the Global North. State-owned enterprises (SOEs), governed according to sound corporate governance principles, can contribute to sustainable socioeconomic development. Not only enhancing their transparency and accountability, but also positioning them to constructively contribute to achieving the Agenda 2063 aspirations. To understand the extent to which sound corporate governance practices can contribute to SOE effectiveness, a qualitative research approach thematically analyses the disclosures contained in the publicly available annual reports of purposively selected SOEs, in predetermined countries across each of Africa’s nine regional economic communities. The extent of conformance with established corporate governance practices is calculated using a disclosure index developed from global corporate governance frameworks. [1] Ubuntu is a Nguni word representing the core African values, such as respect for all humans, human dignity, sharing, obedience, humility, solidarity, caring, hospitality, interdependence and communalism (Sambala, et al., 2020).